Anthony Eden wobec kryzysu abisyńskiego 1934-1936 - Frankiewicz, Małgorzata (Acta Universitatis Lodziensis. Folia Historica, 2001)
The article refers to the British policy towards Italo-Abyssinian conflict 1934-1936. The study touch the subject with a special emphasis of Anthony Eden’s policy between 1934-1936 in the League of Nations and his efforts to solve the problem of the Italian aggression. The analysis describes conditions witch influenced his activity and policy of the British Government. The Italo-Abyssinian conflict is presented against the background of international relations 1934-1936. The main conclusions of the study are as follows. Eden tried to save the Abyssinian independence and as the best forum for the discussion he choose the League of Nations. He did not achieve his aims because of the British policy of appeasement, Italian superiority over Abyssinia and complicated international situation. Eden was not enough strong personality to force his views and oppose policy of his chiefs. The conflict in Africa confirmed him in the onviction that there was not any possibility to deal with Mussolini. Consequently, he believed that Britain should oppose Duce’s activity. The conviction and misunderstandings with Chamberlain became one of the reason of his resignation. The analysis is chiefly based on the Documents on British Foreign Policy, materials from Public Record Office, I Documenta Diplomatici Italiani and memoirs.